Cultural Crisis, Deteriorating Heritage, and Placemaking: A Study of Rural West Bengal, India - Chatterjee, Babita; Dwivedi, Amrita (ACCB Publishing, 2023)
‘Culture’ denotes the co-shared beliefs, values, ethos, norms, lifeworlds, and activities commonly represent nature-culture reciprocity. In several remote areas of India, folk culture still breaths within its age-old life world. Against this backdrop, the southwestern part of West Bengal, also known as ‘Jangal Mahal’ has been studied in the present research. In this area, approximately 40% of the population directly depends on indigenous sources of livelihood, and they belong to tribal communities like Mahato, Kurmi, Lodha, Santal, Bauri, and others. These native people are culturally distinct and are identified through their folksongs and dance forms, such as Tusu, Kirtan, Baul, Bhadu, and folk dances, such as Chhau, Khati, etc. However, urban spaces and citizens’ choices for entertainment have brought about considerable changes in the culture and life of these people. Resultantly, with the increasing pace, deterioration in the heritage and culture of such groups seems to set in. Thus, this study highlights the changing scenarios of cultural crises, deteriorating heritage values, and placemaking. We have followed participatory methods, including field observation, interviews and group discussions. And a door-to-door survey was conducted in the 12 villages of four districts with a semi-structured survey schedule. Sixty troupes were selected for interview and Focused Group Discussions (FGDs). The findings show that values and cultural practices change over time, thereby losing their identity. The placemaking of popular culture results in a deep crisis in livelihood and lifestyle. People are slowly adopting other modes of earning, which further threaten their culture. This study aims to suggest suitable ameliorative measures to preserve the pristine cultural art forms and safeguard livelihood and skill sets.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: Folk Culture; Global Village; Heritage; India; Indigenous Livelihood; Placemaking; Regional Identity; West Bengal